Gender Inequality and Economic Growth in South Kalimantan - Sopiana, Yunita; Khairina, Melisa; Maulina, Dessy (Universitas Dharma Wacana, 2024)
The purpose of this study is to investigate the relationship between gender inequality and GDP development in several fields, such as health, education, economics, and employment. A panel random effect regression model is used to analyze the data in order to achieve this.This study found that economic growth in South Kalimantan is negatively and significantly affected by gender inequality in education, as indicated by the average ratio of school time. According to the life expectancy ratio, the gender disparity in health has a small but favorable impact on economic growth in South Kalimantan. When the per capita expenditure ratio is used to examine economic disparities in South Kalimantan, a negative and significant effect becomes apparent. Gender imbalance in the workplace considerably retards South Kalimantan's economic growth, as seen by the ratio of women to males in the working force.